PRINSIP TRANSPARANSI DALAM PENGADAAN BARANG DAN JASA PEMERINTAH MELALUI RUILSLAG - Ainuddin - (Unram Law Review, 2017)
The aim of this paper are to understand and analyze the transparency principles on procurement of government goods and services by virtue Presidential Decree No. 4 2015 on Procurement of Goods and Services which is able to applied in the procurement of government goods and services through ruilslag. The research method using a normative legal approach, since the research will examine and analyze various law priciniples and regulation that are related to the transparency principle on procurement of government goods and services by way of ruilslag. The result of this research described deeply the transparency principle on procurement of goods and services according to Presidential Decree No 4 2015 on procurement of goods and services as the fourth amendment of the presidential regulation No.54 2010 that can be applied in the procurement of goods and services through ruilslag in purpose to be acknowledge by the parties/stakeholders regarding to the formulation of government policy, organization and the enterprises on the implementation of ruilslag, in order to achieve the good governance purpose.